2020
DOI: 10.1016/j.jssr.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Can we meet our mission? Examining the professional development of social studies teachers to support students with disabilities and emergent bilingual learners

Abstract: In this paper, we conduct a secondary analysis of The Institute of Educational Sciences’ (IES) 2011-2012 Schools and Staffing Survey (SASS) data, a self-reported, nationally representative database to examine: (a) the average caseload of students with disabilities and emergent bilingual learners within and across social studies content areas, as well how social studies teachers’ caseloads compare with other content area disciplines and (b) the extent and perceived utility of professional development opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Indeed, the percentage of SWD aged 6 to 21 years who spent 80% or more of their day in general education classes has increased from 47% in 2000 to 63% in 2017 (NCES, 2019). Moreover, a new study confirmed that social studies teachers have a higher caseload of SWD compared with their colleagues in mathematics and English language arts (Mullins et al, 2020). The same study also found that less than 40% of these social studies teachers received professional development focused on SWD, and out of those who did receive the professional development, 34% rated it “not useful” (Mullins et al, 2020).…”
Section: Literaturementioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, the percentage of SWD aged 6 to 21 years who spent 80% or more of their day in general education classes has increased from 47% in 2000 to 63% in 2017 (NCES, 2019). Moreover, a new study confirmed that social studies teachers have a higher caseload of SWD compared with their colleagues in mathematics and English language arts (Mullins et al, 2020). The same study also found that less than 40% of these social studies teachers received professional development focused on SWD, and out of those who did receive the professional development, 34% rated it “not useful” (Mullins et al, 2020).…”
Section: Literaturementioning
confidence: 84%
“…Moreover, a new study confirmed that social studies teachers have a higher caseload of SWD compared with their colleagues in mathematics and English language arts (Mullins et al, 2020). The same study also found that less than 40% of these social studies teachers received professional development focused on SWD, and out of those who did receive the professional development, 34% rated it "not useful" (Mullins et al, 2020). As such, a host of special education researchers have turned their attention to designing strategies to support the diversity of learners now included in mainstream social studies classrooms (see De La Paz & MacArthur, 2003;Hintz, 2017;Jordan et al, 2017;Lintner & Kumpiene, 2017;Lintner & Schweder, 2011;Ryan et al, 2019).…”
Section: High-quality Civic Education and Who Gets Itmentioning
confidence: 84%
See 1 more Smart Citation
“…The call for this issue centering on rural social studies specifically asked researchers to consider the demographics of social studies teachers teaching in rural settings. We approached this call with research interests in the professional development of social studies teachers (Allen, 2021;van Hover & Hicks, 2018), exploration of the demographics and characteristics of teachers through secondary analysis of national data sets (Mullins et al, 2020;Williams & Ernst, 2022), and our work as teacher educators at a rural land grant university. Given this, we recognize the necessity of having a clear evidence-based portrait of teacher (and student) demographic and characteristics to inform future practice rather than succumbing to assumptions and stereotypes regarding the rural (and for that matter urban and suburban) populations (Mcardle, 2019).…”
Section: Introductionmentioning
confidence: 99%